Challenges and Sustainability Dynamics of Urban Agriculture in the Savannah Ecological Zone of Ghana: A Study of Bolgatanga Municipality - Kuusaana, Elias D.; Ayurienga, Isaac; Eledi Kuusaana, Joyce A.; Kidido, Joseph K.; Abdulai, Ibrahim A. (Frontiers in Sustainable Food Systems, 2022)
Increasingly, urban land use planning is getting more complex as limited urban spaces are continuously allocated among diverse land uses. From previous urban food system studies in Ghana, it has become apparent that large portions of urban land parcels are unsustainably converted to urban infrastructure. Hence, the sustainability of the food system is significantly threatened by inefficient spatial and infrastructure planning mechanisms that fail to protect urban agricultural zones. Of critical concern is the fact that agricultural land use allocations on planning schemes are easily converted to residential uses under demand driven expropriations. In that respect, this study was undertaken in the Bolgatanga Township to understand how urban dwellers sustain urban agricultural practices within the city. Using field surveys, key informant interviews and GIS mapping, the study found that, the total sizes of agricultural lands have decreased significantly since 1996 as urban Bolgatanga began sprawling from the inner city through to the urban fringes. In the process, agricultural lands have decreased in terms of both size and contiguity at the household level, compelling farmers to create multiple segregated farmlands within residential neighborhoods in the form of compound farms or fenced urban gardens. Hence, some urban farmers continue to rely on undeveloped residential plots and open public spaces in the inner city for production, but they easily lose these as developments in residential neighborhoods intensifies. From the physical development pattern of the city, we conclude that urbanization in agrarian cities will exacerbate the challenges of food production if relevant policy interventions are unavailable to provide for and protect agricultural lands. The study recommends that, food-inclusive planning schemes should be the basis of future physical plans to guide land uses in the peri-urban and rural zones. This will require both political will and community consensus building on the necessity to preserve urban agricultural space to sustain food supply.